EFFICACY VS EFFECTIVENESS OF STATIN IN PRIMARY PREVENTION OF CARDIOVASCULAR DISEASE- META-ANALYSIS - Rajca, Eliza; Giza, Agnieszka; Marzec, Urszula; Cyrkler, Aleksandra; Cieślak, Natalia; Dąbek, Karol; Giza, Paulina; Wymoczył, Karolina; Czyżak, Kamila; Chodkowska, Agata (International Journal of Innovative Technologies in Social Science, 2026)
Cardiovascular diseases continue to be the main cause of morbidity and death globally, and many first atherosclerotic events strike people lacking previous clinical signs of the illness. Primary prevention’s main pharmacological therapy is statins, but differences between their efficacy seen in randomized trials and their effectiveness in clinical practice remain a significant research topic. By combining data from randomized studies, observational studies, and evidence reviews, this study aimed to thoroughly evaluate the link between the efficacy and effectiveness of statins in primary prevention. Included analysis of main cardiovascular endpoints, the need of baseline risk, treatment intensity, and the part adherence played, a meta-analytic integrative approach was used. Independently of the kind of study, the results show a constant decrease in first cardiovascular events risk, therefore supporting the biological and clinical efficacy of statins. While the absolute benefit mostly depended on the baseline risk level, the relative risk decrease was constant across various populations. Studies using data from clinical practice revealed a somewhat smaller effect size than randomized studies, which can be attributed to variations in adherence, population heterogeneity, and implementation variables. Higher treatment intensity was related with higher risk reduction; long-term treatment tolerance’s relevance was paramount here. To be clear, statins are a successful treatment in the first prevention of cardiovascular disease; their most noticeable advantages are seen in individuals with moderate to high risk. Better compliance, accurate risk stratification, and optimization of treatment deployment are all necessary to close the efficacy-effectiveness divide.